Study on Rules of Fault Stress Variation Based on Microseismic Monitoring and Numerical Simulation at the Working Face in the Dongjiahe Coal Mine - Ke Ma; Fuzhen Yuan; Duanyang Zhuang; Quansheng Li; Zhenwei Wang (Shock and Vibration)
Microseismic monitoring technology was used to study the real-time evolution of rock mass damage generated by a working face as it approached a fault in Dongjiahe Coal Mine. The influence of vertical zoning of overlying strata on damage at the fault was analyzed. Numerical simulation using finite element method based on meso-statistical damage theory was used to investigate the nonlinear and nonuniform failure behaviour of the rock mass near the fault. The response of the fault stress to excavation activity and the rule of fault activation were examined. The results show that the fault damage has segmental characteristics. Microcracks are first generated at the fractured zone that is divided into lower, middle, and upper sections, located 30∼70 m, 120∼180 m, and 230∼280 m above the coal seam, respectively. There was also a segmentation phenomenon in the stress response of fault. The risk of fault activation was evaluated by using the ratio of shear stress to the maximum principal stress. When the working face was 260 m and 140 m away from the fault, the activation risk at the upper-middle and lower sections began to increase, respectively. When the fault was within 60 m, the risk of fault activation was highest.